José Somoza: Poetic Prose or Poem in Prose? - Sáenz Arenzana, M.ª Pilar (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The literary climate in the thirties and forties of the nineteenth century created a favourabIe atmosphere for a formal approach ol genres. The literary genre called poem in prose didn’t rise suddenly. The desire for a renewal of poetic diction was preceded by a more lyrical prose. José Somoza (1781-1852) was one of the writers who tried to use prose as a poetic device. This style can be seen in some of his fragments (El risco de la Pesqueruela and Elegía). Startìng from these texts, the critic Pedro Aullón de Haro considers him to be one of the predecessors of "poem in prose" in Spain. Taking into account Aullón’s reflexion, I would like to can his statements in question in this article. Somoza’s style has some features which comply with the requirements of poetic prose. A kind of prose which arouses the reader’s feelings for the autobiographic account of daily life.